Tissue-specific and hormonally regulated expression of a rat alpha 2u globulin gene in transgenic mice. - Soares, V da C (1987)
To investigate the tissue-specific and hormonal regulation of the rat alpha 2u globulin gene family, we introduced one cloned member of the gene family into the mouse germ line and studied its expression in the resulting transgenic mice. Alpha 2u globulingene 207 was microinjected on a 7-kilobase DNA fragment, and four transgenic lines were analyzed. The transgene was expressed at very high levels, specifically in the liver and the preputial gland of adult male mice. The expression in male liver was first detected at puberty, and no expression was detected in female transgenic mice. This pattern of expression is similar to the expression of endogenous alpha 2u globulin genes in the rat but differs from the expression of the homologous mouse major urinary protein (MUP) gene family in that MUPs are synthesized in female liver and not in the male preputial gland. We conclude that these differences between rat alpha 2u globulin and mouse MUP gene expression are due to evolutionary differences in cis-acting regulatory elements. The expression of the alpha 2u globulin transgene in the liver was abolished by castration and fully restored after testosterone replacement. The expression could also be induced in the livers of female mice by treatment with either testosterone or dexamethasone, following ovariectomy and adrenalectomy. Therefore, the cis-acting elements responsible for regulation by these two hormones, as well as those responsible for tissue-specific expression, are closely linked to the alpha 2u globulin gene.